2014
DOI: 10.1089/neu.2013.2952
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging, Behavioral, and Psychological Sequelae of Repetitive Combined Blast/Impact Mild Traumatic Brain Injury in Iraq and Afghanistan War Veterans

Abstract: Whether persisting cognitive complaints and postconcussive symptoms (PCS) reported by Iraq and Afghanistan war veterans with blast- and/or combined blast/impact-related mild traumatic brain injuries (mTBIs) are associated with enduring structural and/or functional brain abnormalities versus comorbid depression or posttraumatic stress disorder (PTSD) remains unclear. We sought to characterize relationships among these variables in a convenience sample of Iraq and Afghanistan-deployed veterans with (n=34) and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
182
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(196 citation statements)
references
References 61 publications
14
182
0
Order By: Relevance
“…It would be beneficial if future studies are designed in a way that enables researchers to reveal the full set of relationships among TBI, PTSD, central auditory processing, sensory processing in general, and cognitive processes such as memory, attention, and executive function. In addition to further testing in these areas, future studies would benefit from attempts to combine these metrics with structural and functional imaging, as such studies have already shown the potential to help dissociate factors such as PTSD from mTBI [23].…”
Section: Discussionmentioning
confidence: 99%
“…It would be beneficial if future studies are designed in a way that enables researchers to reveal the full set of relationships among TBI, PTSD, central auditory processing, sensory processing in general, and cognitive processes such as memory, attention, and executive function. In addition to further testing in these areas, future studies would benefit from attempts to combine these metrics with structural and functional imaging, as such studies have already shown the potential to help dissociate factors such as PTSD from mTBI [23].…”
Section: Discussionmentioning
confidence: 99%
“…The final sample included 41 fetuses with a mean GA Ϯ SD of 26.8 Ϯ 5.9 weeks (range, 18 -38 weeks). To verify the compatibility of MPF measurements using our protocol with previous studies, 4,5,11,12 we also recruited 3 healthy adults (31-and 51-year-old men and a 50-year-old woman). To study the effect of a possible noise bias on MPF measurements, we obtained an additional series of brain scans with variable SNRs from 1 healthy volunteer (a 47-year-old man).…”
Section: Study Populationmentioning
confidence: 94%
“…The MPF is a biophysical parameter describing the amount of macromolecular protons in tissues involved in cross-relaxation with free water showed promising clinical results in adult brain studies 11,12 and has been histologically validated as an accurate quantitative tool for measuring demyelination. 10 The single-point technique 4 also allowed designing an ultrafast MPF mapping protocol for nonbrain applications.…”
mentioning
confidence: 99%
“…Conventional CT and MRI are primarily sensitive to blood from nearby torn capillaries, rather than axonal damage itself, hence they underestimate the presence of DAI, especially in mTBI. New approaches using diffusion tensor imaging (DTI), positron emission topography (PET), and macromelecular proton fraction (MPF) have showed promising capability in detecting injuries and/or abnormalities that are not visible in CT and MRI (e.g., Petrie et al, 2014;MacDonald et al, 2011;Davenport et al, 2012;Shenton et al, 2012).…”
Section: Clinicalmentioning
confidence: 99%